Konsep Ashabah dalam Warisan Islam Menurut Beberapa Hadis Bukhori - Khairunnisa Khairunnisa; Putri Utami; Dwi Noviani, M.Pd.I. (STIKes Ibnu Sina Ajibarang, 2024)
Textually, Islamic inheritance law is one of the most detailed laws mentioned in the Koran, however, resolving the division of inheritance often requires repeated ijtihad by the ulama. One of the important things in the issue of inheritance is the issue of Ashabah. The results of the research concluded that the 'ashabah hadith is categorized as an authentic hadith and can be used as proof regarding the validity of the 'ashabah system in Islamic inheritance. The implementation of the 'ashabah inheritance system does not have discriminatory implications, on the contrary, it actually contains the value of distributive justice, because justice in inheritance is not always measured by the equality of designation between heirs, but is also determined by proportionality based on the size of the burden of responsibility assigned to each heir. , balance between rights and obligations and balance between what is obtained and needs and uses. This research includes a literature review, while the way it works uses descriptive qualitative methods. In this research, several Bukhori hadiths about Ashabah are included in the Ahad Gharib Muslaq Hadith category and meet the criteria for authentic hadiths that can be used as evidence. Judging from the meaning contained in this hadith, there is no discrimination in this hadith and there is no injustice towards women.